Teachings on the nature of mind - Nydahl, Lama Ole (Blue Dolphin, 1993)
This short booklet is a basic introduction to Buddhism for "the intelligent and idealistic West." Here Ole introduces the essential teachings of the Buddha, his life and times, and his great discovery of Four Noble Truths. From this groundwork comes the Great Way, the unity and integration of compassion anad wisdom in daily life, and the Diamond Way, which recognizes the timeless and radiant nature of mind.